Intervention Minimizing Preterm Infants' Exposure to NICU Light and Noise. (August 2013) - Aita, Marilyn; Johnston, Celeste; Goulet, Céline; Oberlander, Tim F.; Snider, Laurie
Neonatal intensive care unit (NICU) light and noise may be stressful to preterm infants. This research evaluated the physiological stability of 54 infants born at 28- to 32-weeks' gestational age while wearing eye goggles and earmuffs for a 4-hour period in the NICU. Infants were recruited from four NICUs of university-affiliated hospitals and randomized to the intervention–control or control–intervention sequences. Heart rate (HR), heart rate variability (HRV), and oxygen saturation (O2 sat) were collected using the SomtéTM device. Confounding variables such as position and handling were assessed by videotaping infants during the study periods. Results indicated that infants had more stress responses while wearing eye goggles and earmuffs since maximum HR was found to be significantly higher and high-frequency power of HRV significantly lower during the intervention as compared with the control period. Therefore, this intervention is not recommended for the clinical practice.